Serum matrix metalloproteinase-8, tissue inhibitor of metalloproteinase and myeloperoxidase in ischemic stroke - Palm, Frederick; Pussinen, Pirkko J.; Safer, Anton; Tervahartiala, Taina; Sorsa, Timo; Urbanek, Christian; Becher, Heiko; Grau, Armin J. (Atherosclerosis, 2018)
Background and aims - Matrix metalloproteinase (MMP)-8 and myeloperoxidase (MPO) may contribute to cerebral damage in acute ischemic stroke. We tested the hypothesis that levels of MPO, MMP-8 and the ratio between MMP-8 and its regulator, tissue inhibitor of metalloproteinase (TIMP-1), are increased in acute ischemic stroke and its etiologic subgroups and they correlate with stroke severity. - Methods - In a cross-sectional case-control study, serum concentrations of MMP-8, MPO and TIMP-1 were assessed within 24h after admission in 470 first-ever ischemic stroke patients and 809 age- and sex-matched controls, randomly selected from the population. Odds ratios (OR) per decade of log transformed dependent variables were calculated and adjusted for age, sex and vascular risk factors. - Results - Levels of MMP-8 (OR 4.9; 95% CI 3.4-7.2), MMP-8/TIMP-1 ratio (3.0; 2.2-4.1) and MPO (6.6; 4.0-11.0) were independently associated with ischemic stroke. MMP-8 levels differed between etiologic stroke subgroups (p=0.019, ANOVA), with higher levels in cardioembolic stroke and stroke due to large vessel disease, and lower levels in microangiopathic stroke. MMP-8, MMP-8/TIMP-1 ratio and MPO (p < 0.001) concentrations showed positive associations with stroke severity independent of stroke etiology. - Conclusions - Concentrations of serum neutrophil markers are increased after ischemic stroke and associate with stroke severity and etiology. The value of these biomarkers in diagnostics and prognostics is worth being evaluated.
Gesehen am 27.02.2020